Astronomy and Feng Shui in Ming Urban Planning: A Satellite and Paleo-Magnetic Based Analysis - Norma Camilla Baratta; Giulio Magli (Remote Sensing)
Chinese urban planning has a millenary history. According to the ancient classic texts, it was based on principles related to the cosmic order as well as on traditional ideas related to the feng shui doctrines. The problem of understanding the extent to which such ideas were put into practice is still open, partially due to the overwhelming number of cities founded or re-founded in the more than 2100 years of Chinese imperial history. In the present work, a new, comprehensive analysis of this issue is presented, with a focus on the Ming period. We construct a database which includes 238 towns—virtually all the cities founded or re-founded by the Ming dynasty—using tools based on satellite imagery to investigate orientations and relationships with natural features, and historical paleomagnetic models to investigate magnetic orientation. The results show the existence of three main “families” of towns, of which one strictly adheres to “cosmic” principles, while the other two are mainly connected to the environment. Magnetic orientation turns out, instead, to be related to the imperial capitals only.